Crystallisation-driven self-assembly of poly(2-isopropyl-2-oxazoline)-block-poly(2-methyl-2-oxazoline) above the LCST1. Issue 17 (7th May 2015) - Legros, Camille; De Pauw-Gillet, Marie-Claire; Tam, Kam Chiu; Taton, Daniel; Lecommandoux, Sébastien
<x xml:space="preserve">Abstract</x> The solution behaviour in water of a polyoxazoline-type block copolymer above the LCST of the poly(2-isopropyl-2-oxazoline) block was exploited to induce a temporary or permanent self-assembly.